Clinical presentation and outcome in a series of 32 patients with 2-methylacetoacetyl-coenzyme A thiolase (MAT) deficiency - Grünert, Sarah; Staufner, Christian; Korenke, Christoph (Molecular genetics and metabolism, 2017)
2-methylacetoacetyl-coenzyme A thiolase (MAT) deficiency, also known as beta-ketothiolase deficiency, is an inborn error of ketone body utilization and isoleucine catabolism. It is caused by mutations in the ACAT1 gene and may present with metabolic ketoacidosis. In order to obtain a more comprehensive view on this disease, we have collected clinical and biochemical data as well as information on ACAT1 mutations of 32 patients from 12 metabolic centers in five countries. Patients were between 23months and 27years old, more than half of them were offspring of a consanguineous union. 63% of the study participants presented with a metabolic decompensation while most others were identified via newborn screening or family studies. In symptomatic patients, age at manifestation ranged between 5months and 6.8years. Only 7% developed a major mental disability while the vast majority was cognitively normal. More than one third of the identified mutations in ACAT1 are intronic mutations which are expected to disturb splicing. We identified several novel mutations but, in agreement with previous reports, no clear genotype-phenotype correlation could be found. Our study underlines that the prognosis in MAT deficiency is good and MAT deficient individuals may remain asymptomatic, if diagnosed early and preventive measures are applied.